Targeting CLDN6 in germ cell tumors by an antibody-drug-conjugate and studying therapy resistance of yolk-sac tumors to identify and screen specific therapeutic options - Margaretha A. Skowron; Mara Kotthoff; Felix Bremmer; Katja Ruhnke; Fatma Parmaksiz; Annika Richter; Stefan Küffer; Kirsten Reuter-Jessen; Stella Pauls; Anja Stefanski; Philipp Ströbel; Kai Stühler; et al. (BMC, 2023)
Abstract Background Being the standard-of-care for four decades, cisplatin-based chemotherapy is highly efficient in treating germ cell tumors (GCT). However, often refractory patients present with a remaining (resistant) yolk-sac tumor (YST(-R)) component, resulting in poor prognosis due to lack of novel treatment options besides chemotherapy and surgery. The aim of this study was to identify novel targets for the treatment of YST by deciphering the molecular mechanisms of therapy resistance. Additionally, we screened the cytotoxic efficacy of a novel antibody-drug-conjugate targeting CLDN6 (CLDN6-ADC), as well as pharmacological inhibitors to target specifically YST. Methods Protein and mRNA levels of putative targets were measured by flow cytometry, immunohistochemical stainings, mass spectrometry of formalin-fixed paraffin-embedded tissues, phospho-kinase arrays, or qRT-PCR. Cell viability, apoptosis and cell cycle assays of GCT and non-cancerous cells were performed using XTT cell viability assays or Annexin V / propidium iodide flow cytometry, respectively. Druggable genomic alterations of YST(-R) tissues were identified by the TrueSight Oncology 500 assay. Results We demonstrated that treatment with a CLDN6-ADC enhanced apoptosis induction specifically in CLDN6+ GCT cells in comparison with non-cancerous controls. In a cell line-dependent manner, either an accumulation in the G2 / M cell cycle phase or a mitotic catastrophe was observed. Based on mutational and proteome profiling, this study identified drugs targeting the FGF, VGF, PDGF, mTOR, CHEK1, AURKA, or PARP signaling pathways as promising approaches to target YST. Further, we identified factors relevant for MAPK signaling, translational initiation and RNA binding, extracellular matrix-related processes as well as oxidative stress and immune response to be involved in therapy resistance. Conclusions In summary, this study offers a novel CLDN6-ADC to target GCT. Additionally, this study presents novel pharmacological inhibitors blocking FGF, VGF, PDGF, mTOR, CHEK1, AURKA, or PARP signaling for the treatment of (refractory) YST patients. Finally, this study shed light on the mechanisms of therapy resistance in YST.